Kontribusi mata pelajaran produktif dalam membangun kesiapan kerja siswa smk di Indonesia - Rosmawati, Rita; Meilani, Rini Intansari (Jurnal Pendidikan Manajemen Perkantoran (JPManper), 2019)
Learning process at the Vocational High Schools (SMK) in Indonesia is specifically intended to prepare their graduates to have necessary knowledge and skills in certain fields and appropriate attitudes to be ready to work immediately after graduation. This article discusses the results of a study aimed at finding out the extent of contribution of achievements on productive subjects provided during the learning process at Vocational Schools to the work readiness of 12th grade Vocational students in a State Vocational School in one of capital cities in Indonesia. By adopting quantitative research methods, data were collected by collecting 144 students ?learning achievements in all productive subjects they had taken in five semesters of their study, and by distributing a set of questionnaires to find out the students' work readiness. The collected data were analyzed using descriptive and inferential statistics analyses. The results of data analyses showed that students? achievements in productive subjects gave positive contribution to students? work readiness. Holistic efforts involving all the elements involved in the learning process in school, which supports the development and mastery of students' knowledge, skills and positive mental attitudes must be carried out comprehensively so that they can achieve maximum achievement and have good work readiness and can work and develop professionally after they have completed their study at Vocational School.ABSTRAKProses pembelajaran yang dilaksanakan di Sekolah Menengah Kejuruan (SMK) di Indonesia secara khusus ditujukan untuk mempersiapkan lulusannya untuk memiliki pengetahuan dan keterampilan pada bidang tertentu dan sikap yang berterima agar siap untuk bekerja setelah lulus. Artikel ini membahas hasil penelitian yang ditujukan untuk mengetahui seberapa besar kontribusi mata pelajaran produktif yang diberikan selama proses pembelajaran di SMK terhadap kesiapan kerja para siswa SMK kelas 12 di sebuah SMK Negeri di salah satu kota besar di Indonesia. Dengan mengadopsi metode penelitian kuantitatif, data dikumpulkan dengan menganalisa hasil belajar 144 siswa dalam semua mata pelajaran produktif yang dipelajari dalam lima semester, serta dengan menyebarkan angket untuk mengukur kesiapan kerja para siswa. Data yang dikumpulkan dianalisa secara deskriptif dan inferensial. Hasil analisis data menunjukan bahwa prestasi siswa pada mata pelajaran produktif memberikan kontibusi yang positif terhadap kesiapan kerja siswa. Usaha holistik yang melibatkan semua elemen yang terkait dalam proses pembelajaran di sekolah, yang mendukung pengembangan dan penguasaan pengetahuan, keterampilan dan sikap mental positif para siswa harus dilakukan secara komprehensif sehingga mereka dapat mencapai prestasi yang maksimal dan memiliki kesiapan kerja yang matang dan dapat bekerja serta berkembang secara profesional setelah mereka menyelesaikan masa studi nya di SMK.